KEPEMIMPINAN EKSPATRIAT DALAM PERUSAHAAN INDONESIA - An Nisa Puspita Dewi; Hanung Eka Atmaja (STIMI Handayani Denpasar, 2021)
This study aims to analyze and describe the leadership of expatriates in Indonesian companies. The sample of this research is articles that have been published by 6 accredited national journals in the years 2010-2020. The sample was obtained as many as 10 articles discussing expatriate leadership. The research method used in this research is qualitative analysis with a literature study approach. Some of the most researched topics are the cross-cultural leadership of expats in companies or agencies. The results of this study indicate that expatriate leadership uses a democratic leadership style. The leader seeks to cooperate with local employees in the decisionmaking process and in the work environment the leader also tries to adapt to new cultures.